EVALUATION OF THE MINIMAL EFFECTIVE FOAM SCLEROSANT CONCENTRATION AT SCLEROTHERAPY OF VARICOSE VEINS IN THE LOWER EXTREMITIES - Khrystyna Korolova (Bogomolets National Medical University, 2019)
Chronic venous insufficiency is a widespread, global problem and continuously progresses with increasing age. Actual is a question of treatment of various classes of chronic venous insufficiency. Today, due to the widespread introduction of instrumental techniques and chemical agents, the era of minimally invasive interventions that compete with classical venectomies has begun. The gold standard for treating the initial manifestations of chronic venous insufficiency is sclerotherapy. It has been used to treat varicose veins since the beginning of the last century. In chemical sclerotherapy, various chemical agents are used, which, first of all, contribute to damage, dehydration and destruction of endothelial cells, which leads to the elimination of veins. All sclerosants are a compromise between efficacy and toxicity. In the scientific world, discussions are still ongoing and there is insufficient clinical data regarding the optimal choice of sclerosant and its concentration. The aim of this study was to study the histopathological changes in the vein wall, which can be caused by different concentrations of foam sclerosants, and to study the main negative side effects that occur in patients treated with these concentrations of sclerosants. Our study included 40 patients who were hospitalized from December 2017 to May 2019 with major varicose veins in combination with reticular varicose veins or telangiectasias (C2 - C4a class of varicose veins according to CEAP classification), patients underwent open venectomy followed by repeated sclerotherapy in distant period. Patients were randomized into 3 main groups of 10 people who were injected with the most common concentrations of polidocanol: 0.5%, 1% and 3%. The comparison group was 10 people with a similar pathology. Polidocanol was injected in foam form the day before surgery - venectomy. During venectomy, previously marked segments of the veins were carefully removed and sent for histopathological examination. general assessment was carried out according to a system that reflected the degree of damage to the vein wall in points. Three weeks after venectomy, all patients underwent sclerotherapy of small veins using sclerosants of the same concentration as before surgery. Clinical evaluation of post-treatment negative events was performed twice: on the second day and in a month. The results of the study confirm that changes in the vascular wall are already caused when using 0.5% foam polidocanol. The most pronounced and profound changes are caused by the action of 3% foam polidocanol, which is accompanied by a large number of negative side effects in the post-treatment period. The most optimal for sclerotherapy of veins with a diameter of 5-7 mm is 1% concentration. When this concentration is injected, there is enough damage to the vein for its further obliteration, which is not accompanied by as many negative manifestations as a higher concentration. The results of the study may be useful for phlebologists who use sclerotherapy to treat the initial manifestations of chronic venous insufficiency.